Hassan Hanafi’s Actual Theology: From Anthropocentrism to Revolution - Firdaus, Dadan; Pauji, Resa Restu (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
Religion in the contemporary era is often predicted to lose its relevance, as human dependency on transcendence is replaced by material progress and routine practices. Theocentric discourse dominates theological studies while social reality receives insufficient attention. This research aims to explain Hassan Hanafi’s concept of actual theology as a liberation-oriented alternative capable of reconnecting faith with concrete social struggle. This research employs qualitative library research using phenomenology as the analytical framework, centered on Hassan Hanafi’s primary text Min al-ʿAqīdah ilā al-Thawrah and supported by his project al-Turāth wa al-Tajdīd. The findings show that Hanafi reconstructs Islamic theology by shifting its epistemological axis from a purely theocentric-dogmatic orientation toward a theological anthropocentrism focused on justice, liberation, and historical agency. The research concludes that Hanafi’s actual theology offers a transformative paradigm: from creed to revolution, from metaphysical doctrines to social emancipation, providing a substantive contribution to contemporary Islamic theological reform. ملخص غالبًا ما يُتوقع أن يفقد الدين في العصر الحديث أهميته مع استبدال الاعتماد البشري على التعالي بالتقدم المادي والروتين. كما تُركز الدراسات اللاهوتية بشكل أكبر على مسألة الله وحده، تاركةً الواقع الاجتماعي البشري دون تطور. تهدف هذه الدراسة إلى شرح المفهوم اللاهوتي الحالي لحسن حنفي كشكل من أشكال لاهوت التحرير الذي يسعى إلى ربط الإيمان بالنضالات الاجتماعية الملموسة. تعتمد هذه الدراسة على مراجعة نوعية للأدبيات وتحليل ظاهراتي من خلال دراسة نقدية لعمله الرئيسي،